The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jhn.12404
|View full text |Cite
|
Sign up to set email alerts
|

Modified body adiposity index for body fat estimation in severe obesity

Abstract: BAI present significant limitations in severe obesity and MBAI was effective for BF estimation in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Corroborating our findings, Bernhard et al [ 11 ] cross-validated BAI-BF% with BIA-BF% as the reference method, and observed large individual errors in the predicted values of BF%. In addition, Geliebter et al [ 10 ] in a study of 19 candidates for pre-bariatric surgery (mean age 32.6 ± 7.7 years), who were non-diabetic women with clinically severe obesity, reported that the BAI-BF% underestimated BF% by up to 2.2% compared with BIA-BF%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Corroborating our findings, Bernhard et al [ 11 ] cross-validated BAI-BF% with BIA-BF% as the reference method, and observed large individual errors in the predicted values of BF%. In addition, Geliebter et al [ 10 ] in a study of 19 candidates for pre-bariatric surgery (mean age 32.6 ± 7.7 years), who were non-diabetic women with clinically severe obesity, reported that the BAI-BF% underestimated BF% by up to 2.2% compared with BIA-BF%.…”
Section: Discussionsupporting
confidence: 88%
“…This outcome was also reflected in our own findings. Nevertheless, it is difficult to compare our results with those of previous research because of the different devices used, such as single-frequency [ 11 , 12 ] vs. multi-frequency instruments [ 10 , 18 ] ( Table 4 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results confirmed BAI as a valid predictor of BF% when compared to data obtained with DEXA. In addition, it has been widely used in hospitals (i.e., patients with non-dialysed chronic kidney disease) [10] and research areas (i.e., patients with severe obesity from Brazil) [11]. Correlation coefficients between parameters of body composition assessed by BAI were highly related to those determined by DEXA or magnetic resonance imaging (r values between 0.62 and 0.96) [1,9,12,13], but several publications have criticized the accuracy of BAI [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for simple indicators of adiposity in the Latin American population, and such indexes may be especially useful to clinicians to estimate health risk or intervention effectiveness in obese adults. BAI was developed and validated in non-Caucasian subjects, and might be adequate in populations of Central [15] and South America [11,12]. To our knowledge, no previous study has compared BAI with DEXA in the detailed assessment of body composition for obese adults of the Colombian population [22,23].…”
Section: Introductionmentioning
confidence: 99%